PESAN DAKWAH DALAM FILM “AIR MATA DI UJUNG SAJADAH” - Hafifah Intan Rahmadiani; Nazar; Siti Misbah; Fadillah Ulfa (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2025)
Dakwah messages are those that encompass the principle of Amar Ma’ruf Nahi Mungkar. Utilizing evolving technology, such as audiovisual media in films, is an effective means of conveying dakwah. This study aims to explain the content of dakwah messages in the film